Sphaerialactonam, a γ-lactam–isochromanone from the Hawaiian endophytic fungus Paraphaeosphaeria sp. FT462. Issue 13 (29th March 2017) - Huang, Peng; Li, Chunshun; Sarotti, Ariel M.; Turkson, James; Cao, Shugeng
Graphical abstract: Highlights: Sphaerialactonam with a unique structure has not been reported before. NMR calculation was utilized to determine the stereochemistry of sphaerialactonam. The biosynthesis of sphaerialactonam has been proposed. Abstract: Reinvestigation of the endophytic fungus Paraphaeosphaeria sp. FT462 from the Hawaiian plant Lycopodiella cernua (L.) Pic. Serm led to the isolation and identification of a unique γ-lactam-isochromanone (1 ). The structure of1 was determined by NMR, MS spectroscopic analysis, and quantum chemical calculations of NMR. The compound was tested inactive against A2780 and A2780cisR.